Strategi Bauran Promosi Penyelenggaraan Event (Studi Kasus Perencanaan dan Penyelenggaraan Event Pasar Murah) - Yunita, Linda Desma; Handayani, Tri (Jurnal Riset Bisnis dan Investasi, 2018)
The purpose of this event is to find out the promotion mix strategy used in the implementation of the Pasar Murah event either promotion to the public or to the promoter / sponsor. This project implementation method consists of several steps; project preparation, project implementation, project completion, and project reporting. At the stage of project preparation, the project concept is determined, the establishment of the committee, and the project proposal. At the stage of project implementation, the determination of the participants and sponsors, and to do the promotion strategy. At the completion stage of the project carried out the implementation of the event Pasar Murah. At the stage of project reporting carried out is the reporting of the project promotion strategy. Promotion strategy used in this project is to implement promotion mix that is, personal sales, advertising, sales promotion.